The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3233/jad-200640
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation for Apathy in Alzheimer’s Disease: A Double-Blind, Randomized, Sham-Controlled Pilot Study

Abstract: Background: Apathy, a profound loss of motivation, initiation, and goal directed cognition, is a common comorbidity of Alzheimer’s disease (AD). The presence of apathy is associated with rapid progression of AD, long-term impairment, disability, and higher mortality. Pharmacological treatments of apathy are limited. Objective: The primary objective was to evaluate the efficacy of repetitive transcranial magnetic stimulation (rTMS) for apathy in AD. Methods: A randomized, double-blind, parallel-arm, sham-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 58 publications
1
42
1
1
Order By: Relevance
“…A study by Turriziani et al (2019) used 1 Hz, and the other 6 studies used 10 Hz ( Rabey et al, 2013 ; Leocani et al, 2020 ; Padala et al, 2020 ; Jia et al, 2021 ; Vecchio et al, 2022 ). The dorsolateral prefrontal cortex (DLPFC) was selected as the stimulation site in the majority of studies (10/14) ( Cotelli et al, 2011 ; Ahmed et al, 2012 ; Rabey et al, 2013 ; Wu et al, 2015 ; Turriziani et al, 2019 ; Zhang et al, 2019 ; Bagattini et al, 2020 ; Padala et al, 2020 ; Li et al, 2021 ; Vecchio et al, 2022 ). Rabey et al (2013) and Vecchio et al (2022) stimulated Broca, Wernicke, L/R-DLPFC, and L/R pSAC.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Turriziani et al (2019) used 1 Hz, and the other 6 studies used 10 Hz ( Rabey et al, 2013 ; Leocani et al, 2020 ; Padala et al, 2020 ; Jia et al, 2021 ; Vecchio et al, 2022 ). The dorsolateral prefrontal cortex (DLPFC) was selected as the stimulation site in the majority of studies (10/14) ( Cotelli et al, 2011 ; Ahmed et al, 2012 ; Rabey et al, 2013 ; Wu et al, 2015 ; Turriziani et al, 2019 ; Zhang et al, 2019 ; Bagattini et al, 2020 ; Padala et al, 2020 ; Li et al, 2021 ; Vecchio et al, 2022 ). Rabey et al (2013) and Vecchio et al (2022) stimulated Broca, Wernicke, L/R-DLPFC, and L/R pSAC.…”
Section: Resultsmentioning
confidence: 99%
“…175 Another double-blind, sham-controlled, parallel arm, randomized study of rTMS in older subjects with Alzheimer's dementia and apathy (N=20) showed significant improvement in motivation for rTMS compared to sham treatment after twenty treatments. 176 Additionally, there was also significantly greater improvement…”
Section: Non-pharmacologicalmentioning
confidence: 95%
“…Am J Geriatr Psychiatry 30:2, February 2022 in cognition, function and clinical global improvement. 176 Another RCT is evaluating the efficacy of a 20-session Cognitive-Behavioral-Treatment program compared to treatment as usual on depression and other NPS (apathy is a secondary outcome) in patients with mild AD, mixed AD and vascular dementia. 177 Further research is also emerging which demonstrates the efficacy of information and communication technology (ICT) approaches such as serious games to improve apathy.…”
Section: Mortby Et Almentioning
confidence: 99%
“…There is preliminary evidence to suggest that rTMS might be effective for attenuating their severity [ 94 ]. A very recent preliminary study of apathy in AD found that stimulation to the left dorsolateral prefrontal cortex was associated with greater improvement in AES-C relative to sham treatment [ 95 ].…”
Section: Therapeutics: Pharmacological and Nonpharmacological Interventionsmentioning
confidence: 99%